Level of follicular fluid vitamin D and embryo quality in a sample of Iraqi women undergoing IVF - Alawad, Zainab M. (Journal of the Faculty of Medicine Baghdad, 2019)
Background: Vitamin D has been linked to fertility since its receptors were found in reproductive organs. Nevertheless, its exact role in fertility is yet to be cleared.Objectives: To analyze follicular fluid (FF) vitamin D in females doing Intracytoplasmic Sperm Injection (ICSI), to compare its level between Polycystic Ovary Syndrome (PCOS) and non-PCOS females, and to explore whether vitamin D correlates with oocytes number, percentage of oocyte maturity, fertilization rate and percentage of high quality embryos.Patients and methods: This comparative observational study was done, from January to October 2018, at Al Amal IVF Center, Jenin hospital, Baghdad. The study was conducted on 40 women; 18 had PCOS, 15 had blocked fallopian tubes and 7 had idiopathic infertility. FF vitamin D was analyzed by Ichroma kit, Boditech. Deficient, insufficient, and sufficient vitamin D levels were as: